An Overview of Microparticulate Drug Delivery System and its ExtensiveTherapeutic Applications in Diabetes - Mona Hassan Rafiee; Bazigha K. Abdul Rasool (Tabriz University of Medical Sciences, 2022)
Microparticulate drug delivery system (MDDS) has attained much consideration in the modernera due to its effectiveness in overcoming traditional treatment problems. Microparticles (MPs)are spherical particles of a diameter ranging from 10 μm to 1000 μm. MPs can encapsulateboth water-soluble and insoluble compounds. MDDS proved their efficacy in improvingdrugs bioavailability, stability, targeting, and controlling their release patterns. MPs also offercomfort, easy administration, and improvement in patient compliance by reducing drugstoxicity and dosage frequency. This review elucidates the fabrication techniques, drug release,and therapeutic application of MDDS. Further details concerning the therapeutic applicationsof antidiabetic drugs-loaded MPs were also reviewed, including controlling drugs release bygastroretention, improving drugs dissolution, reducing side effects, localizing drugs to the site ofdisease, improving insulin stability, natural products loaded with MPs, sustained drug release,mucosal delivery, and administration routes. Additionally, the current situation and futureprospects in developing MPs loaded with antidiabetic drugs were discussed.